Exploring the significance of treated wastewater reuse in urban agriculture and resilient cities: a bibliometric analysis - Sei, L. K.; Belle, J.; Mshelia, Z.; Dirwai, Tinashe Lindel (IWA Publishing, 2025)
The sustainability and resilience of a city rely on its capacity to utilize its environmental resources while maintaining social, environmental, and economic balance. Practising urban agriculture (UA) is a sustainable solution that can offset this balance. Treated wastewater (TWW) generated in urban areas can be used to reduce stress on available water resources. However, the extent of its significance remains unclear. This study used bibliometric analysis to explore the trends in publication and thematic evolution between 2008 and 2024 from the Scopus database. The bibliometrics R-package and VOSviewer software were used for bibliometric analysis and science mapping. A total of 1,208 articles were retrieved from the database, from which 960 were used for analysis after data cleansing. The analysis of the results shows that wastewater (WW) reclamation and treatment were found to have the weakest strength and the least number of occurrences. This suggests that researchers did not seriously investigate the use of TWW for UA, thus suggesting a potential gap in the literature that needs to be addressed. Risk reduction strategies for WW reuse in UA were also discussed. This paper argues that reusing TWW for UA can strengthen urban resilience while protecting environmental resources.